2013
DOI: 10.1186/2193-1801-2-59
|View full text |Cite
|
Sign up to set email alerts
|

Empiric mathematical model for predicting the content of alpha-acids in hop (Humulus lupulus L.) cv. Aurora

Abstract: The aim of this research is to find a simple mathematical model due to sum of effective temperatures and rainfalls from second germination after spring pruning till the technological maturity of hop cones, in order to achieve reliable prognosis of alpha-acids content in hop cv. Aurora. After mathematical analyses of experimental data by Eurequa Formulize 0.96 Beta software 17 equations were offered, and after substituting the values of dependent and independent variables in all equations only one equation was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 6 publications
1
6
1
1
Order By: Relevance
“…However, in our samples, a correlation between α‐acids content and temperature is not present (Tables and ). In other studies, an influence of rainfall on α‐acids content was found, but such data are not confirmed in our study, where no such trend is highlighted (Tables and 4). Although no correlation was found in our study, bitter acids and xanthohumol analysis showed significant differences among Cascade samples, thus confirming the important role of the geographical origin on the production of these compounds, even if the differences are not related to the parameters taken into consideration.…”
Section: Resultscontrasting
confidence: 99%
“…However, in our samples, a correlation between α‐acids content and temperature is not present (Tables and ). In other studies, an influence of rainfall on α‐acids content was found, but such data are not confirmed in our study, where no such trend is highlighted (Tables and 4). Although no correlation was found in our study, bitter acids and xanthohumol analysis showed significant differences among Cascade samples, thus confirming the important role of the geographical origin on the production of these compounds, even if the differences are not related to the parameters taken into consideration.…”
Section: Resultscontrasting
confidence: 99%
“…It must be however stated clearly that these preliminary results need confirmation after multi-year growing, also to estimate more properly the effects of local conditions for hop cultivation in Italy, but a fingerprint of the phytochemical profile in genetically different wild accessions represents a first, fundamental step to succeed in breeding improvement. (Mozny et al, 2009;Kucera and Krofta, 2009;Srecec et al, 2013;Pavlovic et al, 2013). Finally, our screening suggest that, from a phytochemical standpoint, the content of prenylflavonoids and phloroglucinols in commercial hop cultivars grown in Italy is in agreement with the percentages obtained in countries dedicated to hop cultivation, and therefore a commercial cultivation of hop could be suitable if these data are confirmed.…”
Section: Discussionsupporting
confidence: 81%
“…The reported differential effects of temperature and water availability might be related to the time points of the different phenological stages as the described effects of temperature (negative effect) and water supply (positive effect) are most relevant during flowering, cone formation and early ripening, i.e., before the strongest accumulation of alpha-acids. In general, results on trends of alpha-acids showed differences in relation with cultivar, location and climate conditions, mainly from vegetative stages until early ripening stages (Srečec et al, 2008(Srečec et al, , 2013Pavlovic et al, 2012Pavlovic et al, , 2013Potop, 2014).…”
Section: Impacts Of Hop Transpiration On Hops Yield and Qualitymentioning
confidence: 99%